Epidemiology of peste des petits ruminants in selected districts of Borena zone, Ethiopia - Kumbe, A.; Negussie, H.; Getachew, Y.; Alemu, Biruk; Alemayehu, Gezahegn; Girma, S.; Sibhatu, D.; Emiyu, K.; Waktole, H.; Leta, S. (Springer, 2024)
Background: Peste des petits ruminants (PPR) is a contagious disease caused by the peste des petits ruminants virus (PPRV). The disease poses a significant economic threat to small ruminant production in Ethiopia, particularly to the striving pastoral production system. A cross-sectional study was conducted to estimate the seroprevalence and associated risk factors of PPR in the small ruminants of the Borena Zone. A total of 384 serum samples were collected randomly from sheep and goats and examined for the presence of PPRV antibodies using competition enzyme-linked immune sorbent assay (c-ELISA). Additionally, a retrospective analysis of five years of outbreak data was performed to provide insight into the spatial and temporal distribution of the disease.